2020
DOI: 10.1148/radiol.2020202422
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Observational Study of Brain MRI Findings in Patients with Acute SARS-CoV-2 Infection and Neurologic Manifestations

Abstract: Key Results 1. Of the 73 patients who presented neurological symptoms, 43 had pathological MRI findings (58.9%), including 17 with acute ischemic infarcts (23.3%), 1 with a deep venous thrombosis (1.4%), 8 with multiple microhemorrhages (11.3%), 22 with perfusion abnormalities (47.7%), 3 with restricted diffusion foci within the corpus callosum consistent with cytotoxic lesions of the corpus callosum (CLOCC, 4.1%). 2. Imaging patterns possibly related to COVID-19 were observed in patients in intensive care and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
230
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 148 publications
(242 citation statements)
references
References 38 publications
9
230
0
3
Order By: Relevance
“…An updated literature search for studies published between July 30, 2020 and October 9, 2020 resulted in 346 studies, of which seven studies met the same eligibility criteria [ [27] , [28] , [29] , [30] , [31] , [32] , [33] ]. Overall, 21 articles with a total of 2125 patients were included [ 4 , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ]. No additional eligible study was found after a search of references within the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…An updated literature search for studies published between July 30, 2020 and October 9, 2020 resulted in 346 studies, of which seven studies met the same eligibility criteria [ [27] , [28] , [29] , [30] , [31] , [32] , [33] ]. Overall, 21 articles with a total of 2125 patients were included [ 4 , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] ]. No additional eligible study was found after a search of references within the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 21 studies, all study designs were retrospective, except for two prospective studies [ 28 , 39 ]. Nine studies were multi-center studies [ 4 , 29 , 31 , 33 , 36 , 38 , 40 , 42 , 43 ] whereas the other 12 were performed at single centers [ 27 , 28 , 30 , 32 , 34 , 35 , 37 , 39 , 41 , [44] , [45] , [46] ]. The cohort sizes ranged from 9 to 454 patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…43 Cerebral susceptibility abnormalities (i.e., microbleeds/-thrombosis) were also described as a relatively common neuroimaging feature, particularly in atypical locations such as in the corpus callosum or juxtacortically. [61][62][63][64] Several cases of cerebral venous thromboses have been observed. 56,61 Inflammatory and/or demyelinating syndromes of both the central and the peripheral nervous system have been reported, among them GBS, 53,56,65 ADEM, 53 Miller-Fisher syndrome, and facial nerve palsy (Table S7).…”
Section: Neurological Complicationsmentioning
confidence: 99%